Characteristics of soil carbon and nutrient stocks across land use types in a forest region of central Korea. Issue 3 (3rd July 2017) - Han, Si Ho; Meng, Loth; Park, Gwan Soo; Kim, Se Bin; Cho, Min Seok; Park, Byung Bae
ABSTRACT: Land use change greatly affects the carbon cycling of the Earth. Soil carbon and nutrient stock distributions were identified in the five land use types: Quercus spp. mixed forest (QM); Larix leptolepis plantation (LP); Castanea crenata plantation (CP); Malus pumila orchard (MF); and abandoned fields (AF). Carbon and nutrient concentrations in the organic horizon and the soil were significantly different according to land use type and soil depth. Carbon concentrations of the organic horizon were higher in QM than in AF, while phosphorus concentrations were higher in MF and AF by 7 times and 4 times compared to that in QM and LP, respectively. The total carbon was distributed in A horizon by 51.8% and in B horizon by 38.0%. The amount of phosphorus decreased in the order of MF > AF > CP > LP ≈ QM, showing clear differences among land use types. This research shows that soil carbon and nutrient contents are significantly different across land use types, and it suggests that the horizontal and vertical distribution properties of carbon and nutrients by land use type need to be considered to accurately predict amounts of fixed carbon and nutrients during the transition of farmland to forest.